(untitled) (Journal of Hama University, 2019)
Foliar application was used by Yeast extract with two concentrations (4,8 g/L) and EM-1 with two concentrations (3,4 ml/L) one month pre-harvest fruits during season 2017 and its effect on fruit quality and yeild of persimmon cv. Hachyia. The results showed that the yield of yeast foliar application with concentration (8 g / L) was higher with significant differences in fruit weight which reach to (225 gr) compared with the control (173.5 gr). A significant increase in productivity was observed in yeast extract treatment at concentration (8 g/L)(126.7 kg / tree) while the control was (76.8 kg / tree). In addition, foliar spray with yeast extract (8 g / L) and bio-fertilizer treatments (3 , 4 ml / L) significantly increased the total soluble solids rato compard with the control , While vitamin C was increased by using yeast extract treatmnet with concentration (4 gr /L) and bio-fertilizer with concentration (3 ml / L) which reach to (68.57 , 65.17 mg / 100 gr fresh weight) recpectively compared with the control (35.15 mg / 100 gr fresh weight), However no differences were observed between the treatments in the ratio of reducing sugars and acidity.